(untitled) (Delta Medical College Journal, 2020)
Background: Rheumatoid arthritis (RA) is one of the main causes of disability worldwide. Currently, controversy remains about the best therapeutic alternatives such as complementary and alternative medicine (CAM) and conventional medicine (CM) for this disease when evaluated from a cost effectiveness viewpoint. Objective: To examine the cost effectiveness of CAM and CM in the treatment of RA. Materials and method: The data were collected from Dhaka Medical College Hospital and Government Unani and Ayurvedic Medical College Hospital from August 2008 to February 2009 by primary sources in the study. Total 60 patients were included who had been treated for six months. Patients were assessed with EuroQol 5D (EQ-5D) tool. Results: The outcome is more effective in CAM than CM by EuroQol 5D. The EQ-5D average outcome of CAM is 0.239 and CM is 0.202. The cost of CAM is also lower than that of CM. Conclusion: Our results support that complementary and alternative medicine (CAM) is a more cost-effective option, compared to the conventional medicine for the treatment of RA. Delta Med Col J. Jul 2019 7(2): 76-79